INVESTIGATION OF IRREGULARITY OF YARN PRODUCED IN AN IMPROVED DRAWN TOOL - Dadakhanov, Nurilla; Karimov, Rustamjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
All spinning products, from staple fiber to yarn, are uneven in both linear density and texture. The greater the unevenness, the worse the quality of the product. There are various reasons for unevenness. The impact area of ​​unevenness is the contact length of the crushing roller with the surface of the yarn, which consists of cotton fibers of different thickness and unevenness. The design of an improved stretching tool for ring spinning machines is proposed and researched.